Lordy, aunt Hattie. - Thomas, Ianthe, 1951-; Di Grazia, Thomas (New York, Harper & Row, 1973)
By finding out what kind of day it is, as well as what kind of day it isn$1 (Bt, Jeppa Lee concludes it must be summer.s
Keywords: Summer -- Fiction; African Americans -- Fiction; Southern States -- Fiction